Prevalensi dan Faktor Risiko Penyakit Virus Parvo pada Anjing di Denpasar - Suartha, I Nyoman; Mustikawati, Diana; Krisna Erawan, I Gusti Made; Kayati Widyastuti, Sri (Jurnal Veteriner; Vol 12, No 3 (2011), 2012)
The prevalence and risk factors of canine parvovirus disease in Denpasar were determined using datacollected from private veterinary practioners between 2004-2007. The risk factors observed including :dogs breed, age, sex, vaccination status, season, humidity, and temperature. Diagnosis of parvovirusinfection was done based on clinical signs, confirmed laboratory test and/or rapid test using parvoviruskit. The prevalence of canine parvovirus infection was 3.26% during 2004-2007. It appeared that incompletevaccination would increased the risk of the infection by 10.15 fold (OR 10.15). In addition the risk ofparvovirus infection would increased by 3.09 fold (OR 3.09) when dogs in 0-3 months old in comparison totheese age > 3months. There were not difference in susceptibelity to the infection between male andfemale dogs. Similarly, the occurence of canine parvovirus infection is not significantly affected by season,temperature, and humidity. Whilst the dog breed such as the Rottweiler, Pomeranian, Minipincher, andChihuahua were susceptible to the infection compared to other breed.
Keywords: parvovirus, breed dogs, prevalensi, odds ratio, risk factor